Implementation Of The Analytical Hierarchy Process Method In The Decision Support System In Sorting Assistance For Renovation Of Pre-Prosperous Community House In Sukajadi Village, Perbaungan District - Neswin Yulizar (INFOKUM, 2021)
House Renovation assistance is needed by families of the Pre-Prosperous Community because there are several families who experience a very low economy in Sukajadi Village, Perbaungan District so that the Sukajadi Village Government, Perbaungan District provides house renovation assistance, but with a large number of family heads, the village apparatus must classify data Anyone who is entitled to Home Renovation Assistance, the application of the Analytical Hierarchy Process Method is needed in supporting a house renovation assistance in Sukajadi Village, Perbaungan District, a calculation is needed, with the application of the Analytical Hierarchy Process Method in order to facilitate the Village Apparatus in the process of collecting data for the Head Recipient families of house renovation assistance, so that it can make it easier for the Village Head in determining the Family Head who is entitled to house renovation assistance.